2019
DOI: 10.1016/j.foodchem.2019.05.134
|View full text |Cite
|
Sign up to set email alerts
|

Compositional and morphological analyses of wax in northern wild berry species

Abstract: Aerial surfaces of plants are covered by a waxy cuticle protecting plants from excessive water loss and UV light. In the present study, composition and morphology of cuticular waxes of northern wild berry species bilberry (Vaccinium myrtillus L.), lingonberry (V. vitis-idaea L.), bog bilberry (V. uliginosum L.) and crowberry (Empetrum nigrum L.) were investigated. Scanning electron microscopy (SEM) revealed differences in epicuticular wax morphologies and gas chromatographymass spectrometry (GC-MS) analysis co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 41 publications
5
40
2
Order By: Relevance
“…The chemical composition of ripe WT bilberry fruit cuticular wax corroborates with our previous study (Trivedi et al , 2019a). However, the wax composition showed changes during the course of bilberry fruit development with the proportion of major compound classes generally varying similarly in both WT and GT fruits.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The chemical composition of ripe WT bilberry fruit cuticular wax corroborates with our previous study (Trivedi et al , 2019a). However, the wax composition showed changes during the course of bilberry fruit development with the proportion of major compound classes generally varying similarly in both WT and GT fruits.…”
Section: Discussionsupporting
confidence: 91%
“…The result implies that glossy appearance in GT bilberry fruits could be due to the high reduction in amount of ketones. In supporting this hypothesis, our previous study showed that glaucous appearing bilberry (rod-like epicuticular morphology) and bog bilberry (coiled rodlet morphology) contain ketones while glossy appearing lingonberry and crowberry are devoid of ketones as well as rod-like structures (Trivedi et al ., 2019a). Ketones have earlier been reported to be responsible for the formation of transversely rigid rodlets (Meusel et al ., 1999).…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…The use of anthocyanins as food colourings, especially in more acidic foods, which may favour their stability, has exponentially raised. The exploitation of V. myrtillus fruits for medicine and human diet purposes has gained significant attention, being the economically most important wild berries of Northern Europe, widely used by the food industry [94]. This fruit is consumed not only in a fresh manner, but also in processed products (press cake) and derivatives (juice, jam and liqueur) [95,96].…”
Section: Industrial Applicationsmentioning
confidence: 99%